Pemanfaatan Pekarangan Rumah dengan Budidaya Ubi Jalar untuk Meningkatkan Ketahanan Pangan dan Penghasilan di Sektor Rumah Tangga - Risbarkah, Euis Bayu; Wulandari, Reny; Syifa, Khozanah (AGRITEXTS: Journal of Agricultural Extension, 2025)
Utilization of Home Gardens with Sweet Potato Cultivation to Enhance Food Security and Household Income. Food shortages have led to rising food prices in the market. In response, the government has designated sweet potatoes as a local food crop in East Nusa Tenggara to address Indonesia’s food supply issues. This study aims to determine the productivity of households in growing sweet potatoes and to identify suitable planting methods for yard areas as a means of improving household economics. Data collection was carried out using secondary data from the East Nusa Tenggara Agricultural Statistics Agency. The descriptive process involved understanding the data conditions and explaining them through both numerical and verbal descriptions of the collected variables. The results showed that the highest growth percentage using the single planting method (monoculture) was in Manggarai Regency, while the highest percentage of growth using the mixed planting method (polyculture) was found in East Nusa Tenggara, specifically in South Timor Tengah Regency. Planting crops using the intercropping method can increase the productivity of a variety of crops to be cultivated, as well as help maintain food stability within households.